"How motivation effects job satisfaction" Case study : Primadotnet Holdings Kota Bharu Kelantan. - Mohd Norisham Mohamad Rosli (2015)
The purpose of this case study research on how job motivation affect job satisfaction. The study effects of motivation such as monetary incentives, commission, reward, benefits on performance and job satisfaction related. Posited that different Incentives have different effects on work performance and job satisfaction. Incentives effects on job satisfaction are researched through critical literature review and interview research.